WHAT SHOULD INDONESIA LEARN FROM RIGHTS TO DATA PRIVACY UNDER THE GDPR? - Ravinka, Nadine Arieta; Widiatedja, I Gusti Ngurah Parikesit (Kertha Semaya : Journal Ilmu Hukum, 2022)
Right to data privacy is determined as a fundamental right and shall be protected. The increase of data misuse is an urgent need to legitimize the data protection law. Unfortunately, Indonesia still does not have a comprehensive law regulating personal data protection. This article applied normative legal research methods that draw on statutory and comparative approaches . This article aimed to present the comparison between the GDPR and Indonesia’s PDP Bill by analysing both provisions on data privacy rights. The article indicated that, in the non-existence of comprehensive personal data protection law, the acts carried by the government are not enough to safeguard the data privacy of Indonesia’s citizens. Moreover, there are some deficiencies of the PDP Bill compared to the GDPR. It lacks the substance of the fundamental principles of data protection. This article recommends, in order to strengthen and harmoni s e personal data protection, the government should take proper measures to legalize the personal data protection law immediately which comprises data protection principles in line with international standards.